2014
DOI: 10.1073/pnas.1324043111
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing asthma from a drop of blood using neutrophil chemotaxis

Abstract: Asthma is a chronic inflammatory disorder that affects more than 300 million people worldwide. Asthma management would benefit from additional tools that establish biomarkers to identify phenotypes of asthma. We present a microfluidic solution that discriminates asthma from allergic rhinitis based on a patient's neutrophil chemotactic function. The handheld diagnostic device sorts neutrophils from whole blood within 5 min, and generates a gradient of chemoattractant in the microchannels by placing a lid with c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
83
3
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(92 citation statements)
references
References 57 publications
(52 reference statements)
4
83
3
2
Order By: Relevance
“…Therefore, the CPI is very low, classifying cell movement as no chemotaxis. In case 4, the directness has a value of 0.35, as in an example reported by Sackmann et al (58). An FMI of 0.3 results in an SMI of 0.18, which leads to a low CPI of 0.21.…”
Section: Statistical Analysis Of Haptotactic Behaviormentioning
confidence: 67%
See 1 more Smart Citation
“…Therefore, the CPI is very low, classifying cell movement as no chemotaxis. In case 4, the directness has a value of 0.35, as in an example reported by Sackmann et al (58). An FMI of 0.3 results in an SMI of 0.18, which leads to a low CPI of 0.21.…”
Section: Statistical Analysis Of Haptotactic Behaviormentioning
confidence: 67%
“…5). Thus, it bears these problems like the FMI with the disregard of the x direction of migration as well (58). Directness weights the migration in x and y direction equally, and only information about the ratio of the path length in x and y direction is considered, whereas the overall direction of migration itself is not examined.…”
Section: Statistical Analysis Of Haptotactic Behaviormentioning
confidence: 99%
“…For accurate diagnosis of asthma, a microfluidic device was recently developed that provides an alternative platform for the clinicians to characterize asthma based on the cellular function. They showed that neutrophils move slower than normal in response to inflammation among asthmatics compared to those with allergic rhinitis [26]. Also, COPD correlates well to neutrophil infiltration into airways through chemo tactic migration.…”
Section: Development Of a Diagnostic Systemmentioning
confidence: 99%
“…Microfluidic systems with integrated sensors have been widely used to perform molecular assays on blood samples 24 , capture circulating tumor cells 25 , and detect cancer-specific biomarkers 26 . However, these systems are mainly limited to planar structures and are able to transport liquid over small distances only.…”
Section: Introductionmentioning
confidence: 99%